Telehealth Intervention for Self-management Among Patient with Hypertension: A Scoping Review - I Made Cahyadi Agastiya; Nyoman Eta Risnawati (Jurnal Keperawatan Malang, 2024)
Background: Self-management among hypertensive patients is important to reduce morbidity and mortality. The use of telehealth can be applied to optimized self-management among hypertensive patients. Purpose: This study aimed to describe the application of telehealth in self-management of hypertensive patients. Methods: This review uses three electronic databased namely PubMed, EbscoHost and Scopus. The article included in the review is the use of telehealth in management in hypertensive psien. Review papers are excluded from the review. 9 articles are included in this review. Result: The form of application of telehealth in the management of hypertensive patients is health education related to hypertension, blood pressure monitoring, motivational support related to self-management, reminders in the form of taking medication, doctor visits, and diet, recording blood pressure results regularly in the form of charts / diagrams, and online consultations. Implication: The forms of telehealth implementation in this review are education, monitoring the blood pressure of hypertensive patients, motivation, reminders, diagram of blood pressure monitoring, and e-consultation. Although in the application of telehealth, there are some challenges, the application of telehealth provides advantages and benefits in chronic patient management Keywords: Hypertension; self-management; telehealth